Pengaruh Promosi, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Hp Apple (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Unisma Malang Angkatan 2018) - Bilal Muqtadin; Agus Widarko; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis research was conducted at the Faculty of Economics and Business, Islamic University of Malang Jl. Major General Haryono No. 193 Lowokwaru District, Malang City, East Java 65144. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of promotion, price and product quality on purchasing decisions. The independent variables used are promotion, price and product quality, the dependent variable is the purchase decision. The sample used in this study were 100 respondents who were consumers of Apple HP products. Data collection techniques using a questionnaire. The analytical method used is instrument test, path analysis, f test and t test of determination using IBM SPSS computer software for data processing. The results of this study indicate that promotion, price and product quality have a direct effect on purchasing decisions. Keywords: Promotion, Price, Product Quality, Purchase Decision.